Seasonal Variation in Density, Growth rate and Calcium carbonate Accumulation of Halimeda macroloba Decaisne at Tangkhen Bay, Phuket Province, Thailand - Sinutok, Sutinee; Pongparadon, Supattra; Prathep, Anchana (Malaysian Journal of Science, 2008)
Seasonal variations in density, growth rate and calcium carbonate accumulation of Halimeda macroloba Decaisne, a dominant green alga at Tangkhen Bay on Cape Palma at Phuket province, Southern Thailand, were investigated. There was difference in density of H. macroloba between seasons, 18.72 + 1.68 in the summer and 5.02 + 0.66 thalli.m -2 in the rainy seasons. The higher density of H. macroloba in summer is likely to be the result of delayed effect of asexual propagation by vegetative. fragmentation. Growth rate of H. macroloba at Tangkhen bay, Phuket in summer season was slightly higher than in rainy season. Light availability and photoperiod were higher in the summer season that might increase growth rate by increasing photosynthesis rate in Halimeda plants. There was difference in percentage of calcium carbonate accumulation in H. macroloba between rainy and summer seasons (P <0.05). This might be a result of high light availability in summer season which might increase photosynthesis and growth rate in Halimeda plant. Moreover, high phosphate concentration in rainy season might inhibit calcium carbonate precipitation.